Helicobacter pylori screening: options and challenges. (2nd April 2016) - Venerito, Marino; Goni, Elisabetta; Malfertheiner, Peter
ABSTRACT: Helicobacter pylori gastritis is the most frequent infectious disease in the gastrointestinal tract. Clinical sequelae of the infection including peptic ulcer disease, sporadic gastric cancer (GC) and primary B-cell gastric lymphoma (MALT-lymphoma) may develop in up to 20% of the infected individuals. The H. pylori screen-and-treat strategy is addressed to members of communities with high GC incidence, and first-degree relatives of GC patients. For primary GC prevention, H. pylori screen-and-treat is most effective in patients without precancerous conditions. In populations at moderate risk, strategies for GC prevention need to be explored. A special clinical scenario for primary and secondary prevention of H. pylori related benign complications are patients on non-steroidal anti-inflammatory drugs and low-dose aspirin. Vaccination represents another option for eliminating H. pylori infection in the population and a new H. pylori vaccine has shown promising results. However, long-term effects with the use of vaccine are not available.